CULTURAL ATTRACTIONS, FACILITIES, ACCESSIBILITY, AND REPEAT VISIT TOURISTS IN HALAL TOURISM - MARTA VINA SEFIRA; ROMY YUNIKA PUTRA (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This study aims to determine the effect of tourist attractions, facilities, and accessibility on interest in repeat visits among Istano Basa Pagaruyung tourists in Tanah Datar Regency. This type of research is called quantitative research. The data source in this research is primary data. The data collection method uses a questionnaire distributed to all visitors to the Istano Basa Pagaruyung tourist attraction, Tanah Datar Regency. The number of samples used amounted to 102 respondents, and the primary data was analyzed using the Structural Equation Model (SEM) data analysis technique with the help of the SmartPLS application program. The results of this study indicate that cultural attractions have a positive and significant effect on interest in repeat visits, facilities have a positive and significant impact on interest in repeat visits, and accessibility has a positive and significant impact on interest in repeat visits.